2006
DOI: 10.1186/1472-6882-6-10
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation of a curcuminoid formulation

Abstract: BackgroundCurcumin is the major yellow pigment extracted from turmeric, a commonly-used spice in India and Southeast Asia that has broad anticarcinogenic and cancer chemopreventive potential. However, few systematic studies of curcumin's pharmacology and toxicology in humans have been performed.MethodsA dose escalation study was conducted to determine the maximum tolerated dose and safety of a single dose of standardized powder extract, uniformly milled curcumin (C3 Complex™, Sabinsa Corporation). Healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
791
3
21

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,137 publications
(830 citation statements)
references
References 10 publications
15
791
3
21
Order By: Relevance
“…An increasing number of studies have shown curcumin anticancer efficacy in preclinical and clinical settings (17). Several phase I clinical studies have also shown that curcumin was well tolerated up to 10 to 12 g (17,50). Furthermore, the combination of curcumin and TRAIL resulted in considerable apoptosis in tumors that do not express Bax such as Burkitt's lymphoma, which confers resistance to many conventional chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown curcumin anticancer efficacy in preclinical and clinical settings (17). Several phase I clinical studies have also shown that curcumin was well tolerated up to 10 to 12 g (17,50). Furthermore, the combination of curcumin and TRAIL resulted in considerable apoptosis in tumors that do not express Bax such as Burkitt's lymphoma, which confers resistance to many conventional chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oral intake of 8 g/d curcumin resulted in f2 Amol/L concentration in serum (56). A recent report detected low levels of curcumin after 8 g of oral dose, but it could be because of the type of formulation used, which had 66% less curcumin than the pure curcumin powder (57). Therefore, curcuminoid intake can be expected to result in concentrations high enough to increase the levels of the anticancer drugs in the cells through its inhibitory effect on ABCG2.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects include antioxidant [27], anti-inflammatory [24,28,29], anticarcinogenic and antimicrobial [30][31][32], hepatoprotective [32], thrombosuppressive [33], cardiovascular (i.e., as protection against myocardial infarction) [29,34,35], hypoglycemic [36][37][38], and antiarthritic (i.e., as protection against rheumatoid arthritis) [39], The most compelling and key rationale for the continuing traditional therapeutic use of curcumin is its extremely good safety profile. To date, no studies in either animals [40,41] or humans [42] have discovered any toxicity associated with the use of curcumin, and it is clear that curcumin is not toxic even at very high doses.…”
Section: Q4mentioning
confidence: 99%